2002
DOI: 10.1179/026708301225000635
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic recrystallisation phenomena of commercial purity aluminium during friction welding

Abstract: The microstructures of commercial purity aluminium near the friction weld interface were observed by transmission electron microscopy. Large plastic deformation of aluminium occurred near the weld interface and the microstructure of the aluminium was oriented from the centre to the periphery of the weld nugget. The aluminium grains were re® ned, and there were many recrystallised grains which were almost dislocation free. The re® ned grains, which were of size ~1 m m, formed very near the weld interface. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Larger grains were observed in the FZ, while fine grains were noted in the BM section. The fine grains in the FZ were bordered by the coarse grains of the two diverse metal sides due to dynamic recrystallization [64].…”
Section: Metallography and Visual Examinationmentioning
confidence: 99%
“…Larger grains were observed in the FZ, while fine grains were noted in the BM section. The fine grains in the FZ were bordered by the coarse grains of the two diverse metal sides due to dynamic recrystallization [64].…”
Section: Metallography and Visual Examinationmentioning
confidence: 99%
“…5,6) Friction welding is a more classic process than FSW in terms of use of friction phenomenon. Therefore, many researches have been published on mechanical properties, 7,8) microstructures, 9,10) modeling, 11) welding temperature estimation 12,13) and so on in wide variety of materials from steels to ceramics. However, lack of published works on effect of post weld heat treatment (PWHT) will be a serious problem in near future.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the feature of microstructure of friction welding is also grain refinement that is caused by similar mechanism to FSW, that is, dynamic recrystallization. 9,10) However, the grain growth behavior of friction weld joint has not been studied yet. So it is necessary to investigate thermal stability of microstructures made by friction welding.…”
Section: Introductionmentioning
confidence: 99%
“…Such a drastic grain refinement is general phenomenon in friction weld joints, for example, grain size of 1 mm has been reported in the case of friction welded commercial purity aluminum due to the dynamic recrystallization. 13,14) Since the dynamic recrystallization occurs due to hot heavy work, the upset process that has charge of most amount of deformation could play a great role on it. The effect of upset process on the grain refinement is shown in Fig.…”
Section: Microstructural Developmentmentioning
confidence: 99%
“…The authors reported the microstructural developments in friction welded aluminum and magnesium alloys, which were completely different from those by the other solid state bonding processes. [13][14][15] The microstructural changes that are mainly grain refinement would affect on the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%